Protein Kinase CK2: A Targetable BCR-ABL Partner in Philadelphia Positive Leukemias. (30th December 2015) - Morotti, Alessandro; Carrà, Giovanna; Panuzzo, Cristina; Crivellaro, Sabrina; Taulli, Riccardo; Guerrasio, Angelo; Saglio, Giuseppe
Abstract : BCR-ABL-mediated leukemias, either Chronic Myeloid Leukemia (CML) or Philadelphia positive Acute Lymphoblastic Leukemia (ALL), are the paradigm of targeted molecular therapy of cancer due to the impressive clinical responses obtained with BCR-ABL specific tyrosine kinase inhibitors (TKIs). However, BCR-ABL TKIs do not allow completely eradicating both CML and ALL. Furthermore, ALL therapy is associated with much worse responses to TKIs than those observed in CML. The identification of additional pathways that mediate BCR-ABL leukemogenesis is indeed mandatory to achieve synthetic lethality together with TKI. Here, we review the role of BCR-ABL/protein kinase CK2 interaction in BCR-ABL leukemias, with potentially relevant implications for therapy.